Operational Protocol for Prosthetically Guided Reconstruction of Edentulous Sites Using a Custom-Made Technique - Edoardo Brauner; Federico Laudoni; Lucia Terribile; Andrea Bellizzi; Giulia Amelina; Francesca De Angelis; Nicola Pranno; Stefano Di Carlo (Applied Sciences)
The success of dental implant placement and prosthetic reconstruction relies on sufficient bone volume at the implant site. Contemporary implantology integrates prosthetic planning with implant placement, emphasizing the importance of pre-established prosthetic goals. Guided Bone Regeneration (GBR) techniques have become crucial for bone reconstruction. This study explores the use of custom-made GBR membranes, designed through CAD-CAM technology, in 10 patients with severe bone defects. Patients underwent meticulous preoperative planning, in which digital diagnostic wax-ups and RealGUIDE™ software for implant positioning were used. The custom-made membranes, which were designed based on the individual defects, exhibited successful adaptation. Surgical phases involved membrane placement, bone grafting, and subsequent implant placement. Clinical–radiographic follow-ups demonstrated favorable bone gain outcomes, which enabled prosthetic rehabilitation. Despite membrane exposure occurring in 30% of cases, it did not compromise overall success. The study underscores the potential of custom-made GBR membranes in achieving prosthetic goals, though challenges like exposure and the need for a second surgery require further investigations. The results indicate a promising alternative for predictable bone regeneration in complex cases, shedding light on the prosthetically guided approach for optimal functional and aesthetic outcomes.